Evaluation of Microencapsulated Preparation Formulation of Ethanol Extract of Moringa Leaves (Moringa Oleifera) - Nazla Deswita Siregar; Razoki Razoki; Refi Ikhtiari (Sean Institute, 2026)
Indonesia has abundant natural resources, one of which is the moringa plant (Moringa oleifera), known as “The Miracle Tree” due to its high nutritional content and pharmacological properties as an antioxidant, antimicrobial, and anti-inflammatory agent. This study aims to formulate ethanol extract of moringa leaves into microencapsulated preparations to improve the stability of active compounds and protect the active ingredients from stomach acid. The extract was obtained through maceration using 96% ethanol solvent with a yield of 24.42%. The characterization of the crude drug met the Indonesian Herbal Pharmacopoeia standards, and phytochemical screening showed the presence of alkaloids, flavonoids, triterpenoids, steroids, and tannins. The microencapsulation formulation was made using a combination of sodium alginate polymer and chitosan coating with CaCl2 hardening agent in four different extract concentrations. The evaluation of the preparations included stability testing (cycling test), moisture content testing, and buoyancy testing (floating). The stability test results showed that the preparation remained organoleptically stable without significant physical changes during 6 cycles. All formulas met the <5% moisture content requirement, with the 0.75% concentration formula (F4) having the lowest moisture content of 0.26%. In the adhesion test using rat gastric mucosa, the preparation showed good mucoadhesive ability, where the interaction of chitosan in an acidic environment prolonged the retention time of the microcapsules in the stomach. This study concluded that microencapsulation of moringa leaf extract has great potential as a stable and effective drug delivery system.